2012
DOI: 10.1007/s00415-012-6628-x
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of essential tremor: a systematic review of evidence and recommendations from the Italian Movement Disorders Association

Abstract: Essential tremor (ET) is one of the most common movement disorders of adults, characterized by postural and kinetic tremor. It often causes embarrassment and more rarely serious disability, requiring treatment. To assess the current state of knowledge on ET therapy and produce recommendations based on the analysis of evidence the authors reviewed the literature regarding pharmacologic and surgical therapies, providing a quality assessment of the studies and the strength of recommendations for each treatment. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 161 publications
1
75
0
6
Order By: Relevance
“…Previously, Costall et al [18] reported similar effects of dopamine agonists with respect to the tremor induced by harmine (a harmaline metabolite). However, these latter results cast doubt on the usefulness of b-carboline models to screen drugs for ET, due to the lack of any data clearly showing the clinical effectiveness of dopamine agonists [1]. In contrast, the therapeutic effect of atypical neuroleptics in ET is well established [1].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previously, Costall et al [18] reported similar effects of dopamine agonists with respect to the tremor induced by harmine (a harmaline metabolite). However, these latter results cast doubt on the usefulness of b-carboline models to screen drugs for ET, due to the lack of any data clearly showing the clinical effectiveness of dopamine agonists [1]. In contrast, the therapeutic effect of atypical neuroleptics in ET is well established [1].…”
Section: Introductionmentioning
confidence: 95%
“…However, these latter results cast doubt on the usefulness of b-carboline models to screen drugs for ET, due to the lack of any data clearly showing the clinical effectiveness of dopamine agonists [1]. In contrast, the therapeutic effect of atypical neuroleptics in ET is well established [1].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, processes which are under cerebellar controls are abnormal in ET patients such as the presence of intention tremors and oculomotor impairment [9]. The involvement of the cerebellum are also reflected by the high efficiency of deep brain stimulation [9] and gabapentin [10] in reducing tremor, which target the cerebellar outflow and the GABA pathways, respectively.…”
Section: Et Pathogenesismentioning
confidence: 99%
“…Nearly half of the patients either cannot tolerate medications or have refractory, disabling tremor despite medication [31]. Unfortunately there has been no breakthrough development in medical treatment of ET since 4 years, only a few offlabel medications, such as beta blockers or antiepileptics are available for ET.…”
Section: Disease; Kinetic Tremormentioning
confidence: 99%